Konsumsi, kecernaan protein kasar dan serat kasar sapi bali penggemukan pola peternak yang di suplementasi pakan komplit berbasis silase batang pisang - Umbu Wulang Paranding; Sukawaty Fattah; Yohanis Umbu Laiya Sobang (Jurnal Peternakan Lahan Kering, 2019)
The aim of this study is to evaluate the effect of fed on complete feed containing fermented banana stem silage on feed intake, and the digestibility of crude protein and crude fiber of fattening Bali cattle feeding asusually practiced by local (Timorese) farmers. Experimental animals employed in this research were 9 heads of growing male Bali cattle of 1 to 1.5 years old with the body weight ranging from 111 to 136kg with an average of 120.79kg and coefficient variation (CV) 5.72%, were employed. The experimental design used was completely randomized design consisted of 3 treatments and 3 replications. Those treatments were T0: feed as usually offered by the local farmers (leaves of Leucaenaleucocephala, Acacia leucophloea and Ficussp.) + 1kg complete feed without fermented banana stem silage added, T1: feed as usually offered by the local farmers + 1kg complete feed added with 10% fermented banana stem silage, and T2: feed as usually offered by the local farmers + 1kg complete feed added with 20% fermented banana stem silage. Data collected was subjected to Analysis of Variance (ANOVA). The results showed that the effect of treatments on the intake of crude protein and crude fiber, and also on the digestibility of crude protein was significantly (P<0.05), but not significantly (P>0.05) on the digestibility of crude fiber. In conclusion, fed on complete feed with the addition of fermented banana stem silage was significantly decreased the intake of crude protein and crude fiber, and increased the digestibility of crude protein. At level10% the addition of fermented banana stem silage into complete feed resulted in a relatively the same on crude fiber digestibility of fattening Bali cattle.